Development of a research project in the pandemic - COVID 19: theoretical evaluation of the biosorption of toxic metal ions in inactive biomass, using laboratory residues containing Cr6+ and banana peel powder - Lisovski, Letícia; Borges Feijó, Carolina; Vargas Medina, Eliza; Pacheco Paixão, Juliano; Regina Atz , Nara; Felisberto, Regina (Seven Editora, 2023)
The pandemic (COVID-19) resulted in an impediment to carrying out face-to-face activities that were suspended, hampering the development and completion of research that requires experimental procedures. This situation raised the need to find alternatives to overcome this obstacle. For this, it was considered that the acquisition of knowledge through problem-solving strengthens teaching-learning and the student-teacher relationship and is a pedagogical resource in line with the guiding principles for Professional and Technological Education established in the National Curriculum Guidelines, (BRAZIL, 2012; 20121), and with the disciplines of Projects in the technical course in chemistry at IFRS - Campus Porto Alegre/RS. In this context, the students, authors of this article, continued work started before the pandemic, and developed, guided by teachers, this theoretical-practical project that used silver banana peel powder (PCBP) as inactive adsorbent biomass to remove ions Cr6+ from liquid waste which comes from analytical chemistry courses. The use of the peels of this fruit is relevant considering that in 2019 Brazil produced 6.8 million tons of bananas (EMBRAPA, 2019). The banana peels were dried, pulverized, and sieved. Its characterization by IR-spectrophotometry showed proper functional groups for the adsorption process. Dilutions of the laboratory liquid residue containing Cr6+, as well as the adsorption process were also performed. At this point, due to the pandemic (COVID-19), experimental activities were suspended, and analytical tests could not be performed. However, as an alternative, using results published in similar works and theoretical bases obtained in the literature, hypothetical isotherms were constructed, class C and class L that allowed inferences about the potential for biosorption of the metal ion (Cr6+) in the biomass used. This theoretical study presented the potential for new theoretical-practical studies involving other toxic metal ions and different biomass. DOI: https://doi.org/10.56238/tfisdwv1-023